2020
DOI: 10.1111/ajco.13321
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of S‐1 plus oxaliplatin (SOX) and capecitabine plus oxaliplatin (XELOX) as adjuvant chemotherapies for stage II and III gastric cancer after D2 resection: A single‐center retrospective study

Abstract: A retrospective comparison of S-1 plus oxaliplatin and capecitabine plus oxaliplatin as adjuvant chemotherapies for stage II and III gastric cancer after D2 resection in Chinese patients. SOX has similar survival benefits to XELOX and is well-tolerated in Chinese patients with GC following D2 gastrectomy. There was no significant difference in peritoneal metastasis rates in these two groups. Metastatic lymph node ratio was an independent prognostic factor for OS.The clinical data were collected after informed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…The primary endpoint was 5-year OS, whereas the secondary endpoint was 3-year DFS. The present study was performed without considering the chemotherapy regimen, and the results of previous studies, including those of the RESOLVE trial [ 34 48 49 ], support those of the present study. Our results showed that compared to patients who received 4 cycles of chemotherapy, those who received 6 and 8 cycles of chemotherapy could confer significant additional survival benefits.…”
Section: Discussionsupporting
confidence: 86%
“…The primary endpoint was 5-year OS, whereas the secondary endpoint was 3-year DFS. The present study was performed without considering the chemotherapy regimen, and the results of previous studies, including those of the RESOLVE trial [ 34 48 49 ], support those of the present study. Our results showed that compared to patients who received 4 cycles of chemotherapy, those who received 6 and 8 cycles of chemotherapy could confer significant additional survival benefits.…”
Section: Discussionsupporting
confidence: 86%
“…However, there is a lack of prospective studies to determine which regimen is superior. Current studies suggest that XELOX regimen does not result in a greater survival benefit compared with FOLFOX6 regimen [ 37 ], and the SOX therapy has similar survival benefits to XELOX in Chinese patients with GC following D2 gastrectomy [ 38 ]. Additionally, since groups B, C, and D were balanced concerning the receipt of these three regimens, it is likely that differences in the chemotherapy regimen do not explain the differences in survival among the groups.…”
Section: Discussionmentioning
confidence: 99%
“…For the comparison of the effects of SOX and XELOX, a Japanese study showed that XELOX and SOX treatments have similar effects in patients with stage III GC who underwent D2 resection ( 24 ). Subsequently, the RESOLVE study published by ESMO in 2019 showed that the SOX adjuvant chemotherapy for 8 cycles after radical resection of GC D2 is not inferior to XELOX ( 25 ). The results of a recent single-center retrospective study also showed that SOX is as effective as XELOX for patients with GC after radical resection and that there is no significant difference in survival rate in patients receiving the different treatments ( 13 ).…”
Section: Discussionmentioning
confidence: 99%